Nine‐fold symmetry of centriole: The joint efforts of its core proteins. (7th January 2022) - Tian, Yuan; Yan, Yuxuan; Fu, Jingyan
Abstract: The centriole is a widely conserved organelle required for the assembly of centrosomes, cilia, and flagella. Its striking feature – the nine‐fold symmetrical structure, was discovered over 70 years ago by transmission electron microscopy, and since elaborated mostly by cryo‐electron microscopy and super‐resolution microscopy. Here, we review the discoveries that led to the current understanding of how the nine‐fold symmetrical structure is built. We focus on the recent findings of the centriole structure in high resolution, its assembly pathways, and its nine‐fold distributed components. We propose a model that the assembly of the nine‐fold symmetrical centriole depends on the concerted efforts of its core proteins. Also see the video abstract here: https://youtu.be/m4h_3II_WJo Abstract : Multiple categories of factors have been proposed to work interdependently to determine the nine‐fold symmetry of a centriole — proteins that constitute the central hub, the spoke and inter‐spoke proteins, as well as the microtubule wall itself.